Maternal gestational Bifidobacterium bifidum TMC3115 treatment shapes construction of offspring gut microbiota and development of immune system and induces immune tolerance to food allergen - Cheng, Ruyue; Zhang, Yujie; Yang, Yang; Ren, Lei; Li, Jinxing; Wang, Yimei; Shen, Xi; He, Fang (Frontiers in Cellular and Infection Microbiology, 2022)
In this study we aimed to determine whether treatment with maternal Bifidobacterium bifidum TMC3115 could affect the composition of the gut microbiota and the development of the immune system and intestinal tract of offspring, and protect the offspring from IgE-mediated allergic disease. Pregnant BALB/c mice were gavaged with TMC3115 until delivery. Offspring were sensitized with ovalbumin from postnatal days 21 to 49. After maternal treatment with TMC3115, the microbiota of the offspring’s feces, intestinal contents, and stomach contents (a proxy for breast milk) at the newborn and weaning stages exhibited the most change, and levels of immunoglobulin in the sera and stomach contents and of splenic cytokines, as well as the mRNA levels of colonic intestinal development indicators were all significantly altered in offspring at different stages. After sensitization with ovalbumin, there were no significant changes in the levels of serum IgE or ovalbumin-specific IgE/IgG1 in the TMC3115 group; however, IgM, the expression of intestinal development indicators, and the production of fecal short chain fatty acid (SCFA) were significantly increased, as were the relative abundances of Lactobacillus and the Lachnospiraceae NK4A136 group. Our results suggested that maternal treatment with TMC3115 could have a profound modulatory effect on the composition of the gut microbiota and the development of the immune system and intestinal tissue in offspring at different stages of development, and may induce immune tolerance to allergens in ovalbumin-stimulated offspring by modulating the gut microbiota and SCFA production.